Pengaruh Model TGT Terhadap Hasil Belajar Siswa Pada Pembelajaran PKn di Kelas IV SD - Monika, Monika; Indrawati, Tin; Reinita, Reinita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research was supported by the problems found in the field that the students' learning outcomes in Civic Education were less satisfactory and the learning process was still dominated by the teachers as a source of information. The cooperative model of Teams Games Tournament  is one of the alternative models that can be applied in Civic Education class to overcome the problems. Thus, this research was undertaken as an attempt to assess the effect of cooperative learning model of Teams Games Tournament  on the fourth grade students’ learning outcomes in Civic Education at SDN 33 Rawang Barat Padang. This research adopted a quasi-experimental research design with quantitative approach. The instrument for data collection was the written test. The result of the research revealed that the average score of the experimental class which applied cooperative learning model of teams games tournament compared to the control class  showed better achievement. The result obtained from the data showed that there is more positive effect of using Cooperative Learning Model of Teams Games Tournament  toward fourth grade students’ learning outcomes in Civic Education at SDN 33 Rawang Barat Padang. Key words: Cooperative Model Teams Games Tournament , Learning outcomes